Comparison of Stereotactic Body Radiation Therapy for Biopsy-Proven versus Radiographically Diagnosed Early-Stage Non-Small Lung Cancer: A Single-Institution Experience. Issue 3 (May 2015) - Fischer-Valuck, Benjamin W.; Boggs, Hunter; Katz, Sanford; Durci, Michael; Acharya, Sahaja; Rosen, Lane R.
Introduction: Histological confirmation of non-small cell lung cancer (NSCLC) is often required before patients are offered stereotactic body radiation therapy (SBRT) as a treatment option. Many patients, however, are unsuitable to undergo a biopsy procedure because of comorbidity. Our objective is to compare the outcomes of patients with biopsy-proven (BxPr) or clinically/radiographically diagnosed (RadDx) early-stage NSCLC treated with SBRT. Methods: Records of 88 patients treated with SBRT at a single institution were reviewed. Sixty-five patients had BxPr early-stage NSCLC. Twenty-three patients were RadDx with early-stage NSCLC based on an FDG-avid chest nodule on PET scan, serial sequential CT-findings compatible with NSCLC, and consensus of a multidisciplinary team. Outcomes of patients with BxPr and RadDx NSCLC were evaluated in regard to local control, regional lymph node metastasis-free and distant metastasis-free rates, and overall survival using Kaplan-Meier survival curves. Results: Median follow-up for all patients was 29 months (range, 4–82 months). Cumulative local progression-free rate after 3 years for the BxPr group was 93.1% (95% confidence interval [CI], 85.2%-97.6%) and 94.10% (95% CI, 73.2%-97.6%) for the RadDx group (p = 0.98). No differences regarding regional lymph node metastasis-free and distant metastasis-free rates by subgroup were observed. The overall 3-year survival rate for the BxPr group was 59.9% (95% CI, 44.8%-68.2%) and 58.9% (95% CI, 40.1%-77.8%) for the RadDx group (p = 0.46). Conclusions: SBRT is a practical treatment modality for patients with RadDx early-stage NSCLC. Outcomes of patients RadDx with NSCLC mirror the results of patients treated with BxPr disease.